Oxidation of α-Trifluoromethyl and Nonfluorinated Secondary Alcohols to Ketones Using a Nitroxide Catalyst - Politano, Fabrizio; Brydon, William P.; Leadbeater, Nicholas E. (Synthesis, 2023)
A methodology for the oxidation of α-trifluoromethyl alcohols to the corresponding trifluoromethyl ketones is presented. A catalytic quantity of a nitroxide is used, and potassium persulfate serves as the terminal oxidant. The methodology proves effective for aromatic, heteroaromatic, and conjugated alcohol substrates. It can be extended to nonfluorinated secondary alcohols and, in this case, can be applied to a range of aromatic, heteroaromatic, and aliphatic alcohols.
Keywords: oxidation; trifluoromethyl ketones; nitroxide; persulfate; ketones; alcohols